1986
DOI: 10.1037/0012-1649.22.5.627
|View full text |Cite
|
Sign up to set email alerts
|

The balance of employment and motherhood: Longitudinal study of mothers' feelings about separation from their first-born infants.

Abstract: This longitudinal study was an investigation of how older, well-educated mothers of infants come to terms with establishing a balance between maternal and career roles. The focus was on how their preference to be employed or to remain home with their infants affected the development of their anxiety about separation from their infants over the first 1 V-h months of motherhood. On measures of anxiety about separation, career salience, and maternal role investment, 26 mothers who preferred employment were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 13 publications
1
36
0
Order By: Relevance
“…Internal consistency reliability of the PSAS in this sample was similar to earlier studies and indicated that the scale is appropriate for parents of adolescents with type 1 diabetes. The results were consistent with previous research establishing a relationship of SES to maternal separation anxiety in relation to infants but extended these findings to the adolescent stage (DeMeis et al, 1986;Fein et al, 1993;McBride & Belsky, 1988). Lower socioeconomic status may indicate a context of risks and dangers that activates mothers' anxiety about separation.…”
Section: Study Threesupporting
confidence: 93%
See 2 more Smart Citations
“…Internal consistency reliability of the PSAS in this sample was similar to earlier studies and indicated that the scale is appropriate for parents of adolescents with type 1 diabetes. The results were consistent with previous research establishing a relationship of SES to maternal separation anxiety in relation to infants but extended these findings to the adolescent stage (DeMeis et al, 1986;Fein et al, 1993;McBride & Belsky, 1988). Lower socioeconomic status may indicate a context of risks and dangers that activates mothers' anxiety about separation.…”
Section: Study Threesupporting
confidence: 93%
“…Based on this perspective, separation anxiety has been found to vary with maternal, infant, and situational characteristics (Hock et al, 1989;, notably gender of the infant (DeMeis et al, 1986;McBride & Belsky, 1988;Pitzer & Hock, 1992), maternal employment, and socioeconomic status (DeMeis et al, 1986;Fein, Gariboldi, & Boni, 1993;McBride & Belsky, 1988). In particular, separation anxiety of employed mothers of infant sons was greater than that of employed mothers of infant daughters (Pitzer & Hock, 1992).…”
Section: Separation Anxiety and Parents Of Infants And Childrenmentioning
confidence: 95%
See 1 more Smart Citation
“…The abundant research on mothers' anxiety regarding separation from their children supports the belief that maternal anxiety is an important psychological construct and is meaningfully related to both maternal behaviors towards the child and other aspects of maternal personality (e.g., DeMeis, Hock, & McBride, 1986;Hock, Hart, Kang, & Lutz, 2004;Hock, McBride, & Gnezda, 1989;Hock & Schirtzinger, 1992;Lutz & Hock, 1995;McBride & Belsky, 1988). Yet, the familial antecedents of maternal anxiety have not been fully explicated, nor has their impact on children's separation anxiety and their adjustment to kindergarten.…”
Section: Introductionmentioning
confidence: 93%
“…Maternal separation anxiety has been viewed as a rather stable personality disposition that is elicited in a mother's separation from her child (Hock et al, 1989). Several studies have provided evidence that separation anxiety is a traitlike aspect of the maternal personality instead of a type of state anxiety, with maternal separation anxiety for instance being found to demonstrate relatively stable interindividual differences across time and across situations (DeMeis, Hock, & McBride, 1986;Hock et al 1989). Maternal separation anxiety has also been shown to be associated with negative self-representations , low self-esteem (McBride & Belsky, 1988), and depressive symptomatology Hock, Schirtzinger, & Lutz, 1992).…”
mentioning
confidence: 99%